An evaluation of the municipal solid waste management system within City of Tshwane Metropolitan Municipality, in Mamelodi East Township, Gauteng province South Africa - Rendall-Mkosi, Kirstie Margaret (University of Pretoria, 2015)
Dissertation (MPH)--University of Pretoria, 2014.